ISAAC KALIMI, The Retelling of Chronicles in Jewish Tradition and Literature: A Historical Journey. Winona Lake, Ind., Eisenbrauns, 2009. XX + 395 pp. ISBN 978–1–57506–149–8. U$D 59,50 - Krüger, René (2012)
Fil: Krüger, René. Instituto Universitario ISEDET; Argentina